Causes And Factors of Virtualization in Youth Life - Ergasheva Gulnora Oltiboy qizi (Genius Journals, 2022)
Virtualization, which is developing rapidly today, is gaining a new meaning in the spirituality of every state, people, nation, or humanity. In the development of society, "just as every social phenomenon has its pros and cons, so does the process of virtualization. However, we must not forget that along with such achievements, virtualization also poses a spiritual threat to the national ideas, ideologies, beliefs and heritage of some peoples. This article focuses on this issue and the current issues of protecting young people from information attacks on the Internet and social networks
Keywords: Youth; Internet; Information; Globalization